Attitude towards Breast Cancer and Breast Self-Examination in Middle Aged Females at a Tertiary care hospital in Lahore Pakistan - Riaz, Muhammad Waseem; Azam, Muhammad Saad; Ashraf, Shiza; Butt, Nauman Ismat; Waris, Barak; Ghoauri, Muhammad Sohail Ajmal (Majalah Kesehatan Indonesia, 2025)
Breast self-examination (BSE) is an accessible, self-performed screening method for detecting potential changes or abnormalities in the breast such as breast cancer, allowing individuals to familiarize themselves with their normal breast tissue and identify any unusual signs, but it is not a substitute for other breast cancer screening methods like mammograms or clinical exams. The objective of this research was to assess attitudes towards Breast Cancer and BSE in middle aged females from Lahore Pakistan.This descriptive cross-sectional study was conducted at OPD of Chaudhary Muhammad Akram Teaching and Research Hospital, Azra Naheed Medical College Superior University Lahore Pakistan. Fifty females attending OPD of the hospital, aged 35 to 45 years were enrolled in the study after taking informed consent using non-probability consecutive sampling technique. Females with a present or past diagnosis of breast abnormalities (cysts, mastitis, benign or malignant tumors) were excluded from the study. Demographic information was noted and then the participants filled a structured questionnaire comprising of 3 domains: first domain was regarding attitude towards Breast Cancer; second domain was about attitude towards BSE; while the third domain focused on BSE and mammography practices. All the data was entered and analyzed through SPSS version 26. Majority of the females were aged 35 to 40 years (33, 66.0%). Based on socioeconomic background, 19 (38.0%) females belonged to middle socio-economic status. Majority of the females (17, 34.0%) were undergraduates on educational status followed by 16 (32.0%) illiterate. Forty (80.0%) were married. In the present study, 37 (74.0%) females had heard about Breast Cancer but only 09 (18.0%) were aware about BSE. Only 09 (18.0%) respondents reported performing BSE while 14 (28.0%) had a history of mammographic scan. Advice from friends (04, 8.0%) was the biggest sources of BSE information. Attitude regarding breast cancer and BSE was poor in our study. Our study highlights the need to promote knowledge and awareness regarding breast cancer and BSE by educational programs, public health messages, seminars and through social media. Targeted public health interventions should be done, including educational campaigns and community outreach, to improve awareness and encourage early detection practices such as BSE and mammography, especially among less educated and lower-income women.